2021
DOI: 10.1177/00914509211060723
|View full text |Cite
|
Sign up to set email alerts
|

Addiction Treatment as Prison Governance: A Critical Discourse Analysis of Methadone Delivery in Kyrgyz Prisons

Abstract: Methadone treatment is prescribed by evidence-based medicine as the most effective tool for the treatment of opioid addiction. Its implementation into high-need prison settings worldwide has been met with challenges, particularly in Eastern Europe and Central Asia where the opioid epidemic continues to expand. To address these impasses to intervention translation, we turn to post-structural approaches to policy analysis. These approaches open space for (re)thinking the ways that translated interventions emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Previous studies have found low uptake of MMT in EECA prisons (Altice et al, 2016), and they have suggested that this may be due to stigmatization of MMT by both staff and incarcerated people (Polonsky et al, 2015;. Studies of Moldovan and other EECA prisons have indicated that prisoner hierarchies enact social stigma against MMT and suppress MMT uptake (Azbel et al, 2021;Cotorobai et al, 2019;Liberman et al, 2021;Otiashvili, 2016). The results of this study show that according to rules by the informal governance (the ponyatiya), methadone is something that only lower-caste individuals access, thus limiting wider uptake.…”
Section: Informal Prison Hierarchies Determine Who Is Permitted To Us...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found low uptake of MMT in EECA prisons (Altice et al, 2016), and they have suggested that this may be due to stigmatization of MMT by both staff and incarcerated people (Polonsky et al, 2015;. Studies of Moldovan and other EECA prisons have indicated that prisoner hierarchies enact social stigma against MMT and suppress MMT uptake (Azbel et al, 2021;Cotorobai et al, 2019;Liberman et al, 2021;Otiashvili, 2016). The results of this study show that according to rules by the informal governance (the ponyatiya), methadone is something that only lower-caste individuals access, thus limiting wider uptake.…”
Section: Informal Prison Hierarchies Determine Who Is Permitted To Us...mentioning
confidence: 99%
“…The anticipated social consequences of engaging in MMT are also believed to shape MMT acceptance , yet the social context of access to MMT in prisons in Moldova, EECA, and elsewhere is poorly understood. In Moldova and other EECA countries, informal governance by prisoner hierarchies exerts control over the social order of prison communities by monopolizing and pooling resources, including access to drugs (Azbel, 2020;Azbel et al, 2021;Butler et al, 2018;Gasparyan et al, 2018;Kupatadze, 2014;Liberman et al, 2021). This informal governance operated by a caste system (i.e., hierarchies) of prisoners can compensate for the limited resources (e.g., food, personal hygiene, etc.)…”
Section: Implementing Methadone Maintenance Treatment In Criminal Jus...mentioning
confidence: 99%
“…A recent study of methadone treatment in carceral settings in, however, found a remarkably low linkage to treatment post-release, but for those who were released on methadone, higher dosage was correlated with linkage to and retention on treatment ( Bachireddy et al, 2022 ); increased dosage was similarly associated with higher retention in treatment after release in Malaysia ( Wickersham et al, 2013 ). These findings are especially important given the social hierarchy within Kyrgyz prisons, that lowers the social status of those who enroll on methadone and limit access to prison community resources ( Azbel et al, 2022 ). Prospective trials in the U.S. show low linkage to MMT after release, especially for those not started on methadone while still incarcerate ( Kinlock et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the criminal subculture provides necessary resources to PDL like personal goods that are not provided by the formal prison authorities ( 25 ). Though the social order that evolves among PDL is not entirely unique to post-Soviet nations, its presence in Ukraine ( 26 , 27 ), Moldova ( 21 ), and Kyrgyzstan ( 28 ) is a particular phenomenon ( 29 ). In Moldova and Kyrgyzstan, where methadone treatment provided in prison has been present for nearly two decades, criminal subculture is described as especially powerful, and it has greatly inhibited OAT uptake ( 19 , 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Though the social order that evolves among PDL is not entirely unique to post-Soviet nations, its presence in Ukraine ( 26 , 27 ), Moldova ( 21 ), and Kyrgyzstan ( 28 ) is a particular phenomenon ( 29 ). In Moldova and Kyrgyzstan, where methadone treatment provided in prison has been present for nearly two decades, criminal subculture is described as especially powerful, and it has greatly inhibited OAT uptake ( 19 , 28 ). Little data about these hierarchies in Ukrainian prisons exist and as MMT is being expanded to other prisons there, it will be crucial to understand how these informal hierarchies work and how, if at all, they may influence MMT uptake in Ukrainian prisons.…”
Section: Introductionmentioning
confidence: 99%